Effects of Recombination Rate and Gene Density on Transposable Element Distributions in Arabidopsis thaliana - Wright, Stephen I.; Agrawal, Newton; Bureau, Thomas E. (Genome research, 2003)
Transposable elements (TEs) comprise a major component of eukaryotic genomes, and exhibit striking deviations from random distribution across the genomes studied, including humans, flies, nematodes, and plants. Although considerable progress has been made in documenting these patterns, the causes are subject to debate. Here, we use the genome sequence of Arabidopsis thaliana to test for the importance of competing models of natural selection against TE insertions. We show that, despite TE accumulation near the centromeres, recombination does not generally correlate with TE abundance, suggesting that selection against ectopic recombination does not influence TE distribution in A. thaliana . In contrast, a consistent negative correlation between gene density and TE abundance, and a strong under-representation of TE insertions in introns suggest that selection against TE disruption of gene expression is playing a more important role in A. thaliana . High rates of self-fertilization may reduce the importance of recombination rate in genome structuring in inbreeding organisms such as A. thaliana and Caenorhabditis elegans .